Keefektifan Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar IPA Siswa Kelas IV SD Negeri 39 Woja - Rizka Awaluddin (STKIP Al-Amin Dompu, 2023)
This type of research is quantitative, namely using experimental research methods. The research design is a quasi-experimental form of the Posttest Only Control Group Design. The research sample was taken using simple random sampling technique. This research was conducted four times in each group. Data collection techniques in this study include interviews, observation, documentation and tests. The data analysis technique used in processing the research data is the analysis prerequisite test including normality and homogeneity, and the final analysis. In the final analysis or testing the research hypothesis used is the t-test using the SPSS computer program. Based on the hypothesis test on learning outcomes data obtained a Sig (2-tailed) value of 0.002 (p <0.05), so it can be concluded that there is a significant influence of the guided inquiry learning model on student learning outcomes. Based on the research results, it can be concluded that the guided inquiry learning model is more effectively applied in science learning in class IV students at SDN 39 Woja compared to the conventional learning model. So Ho is rejected and Ha is accepted. The suggestion that can be conveyed is that the guided inquiry learning model can be applied to science learning so that learning is more meaningful. In addition, the guided inquiry learning model can also be applied to other subjects. In order for guided inquiry learning to be operational, the study group members should not exceed 4 people and the teacher should limit the time when carrying out experimental activities.